The Philosophy of pornography contemporary perspectives - Coleman, Lindsay 1978-; Held, Jacob M. 1977- (Rowman & Littlefield, 2014)
"In The Philosophy of Pornography: Contemporary Perspectives, Lindsay Coleman and Jacob M. Held offer a collection of essays covering a wide range of viewpoints--from issues of free speech and porn's role in discrimination to the impact of porn on sexuality. These essays investigate the philosophical implications of pornography as a part of how we now seek to conceive and express our sexuality in contemporary life."--back cover